Socioeconomic and Maternal Predictors of Toddler Malnutrition: Evidence From Rural Indonesia - Usti Fina Hasanah Hasibuan; Meity Christiani (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Deli Serdang Regency in North Sumatra remains a priority area for malnutrition interventions due to persistent socioeconomic disparities, under-resourced rural health systems, and chronic food insecurity. Although national data (Riskesdas 2018) report a stunting prevalence of 21.3%, localized health surveillance in villages such as Tanjung Anom indicates rates exceeding 30%, highlighting elevated nutritional risk among toddlers. A matched case-control study was conducted involving 64 toddlers aged 12-59 months (32 malnourished, 32 well-nourished), matched 1:1 by age group and gender. Malnutrition was defined according to WHO anthropometric Z-scores (< -2 SD for weight-for-age or height-for-age). Data collection included direct anthropometric measurement and structured maternal interviews, incorporating a 24-hour dietary recall. Conditional logistic regression was employed to account for matching, and standardized protocols were implemented to minimize selection and information bias. After adjusting for confounders, four key risk factors were significantly associated with malnutrition: poor maternal nutritional knowledge (adjusted OR = 3.91; 95% CI: 1.18-12.95; p = 0.026), low household income (aOR = 10.23; 95% CI: 2.00-52.39; p = 0.005), recent infectious disease (aOR = 6.11; 95% CI: 1.79-20.84; p = 0.004), and insufficient food intake (aOR = 72.30; 95% CI: 12.98-402.61; p < 0.001). The wide confidence interval for dietary intake reflects limitations in sample size and variability in exposure. This study is among the first matched case-control investigations in rural North Sumatra to quantitatively link maternal nutrition knowledge with child nutritional status using localized data and WHO standards. The findings underscore the need for targeted, nutrition-sensitive interventions, including strengthening Community Health Post (Posyandu) services, enhancing maternal nutrition education, promoting community home gardens, and improving rural health infrastructure. This model offers potential for scale-up through multisectoral collaboration and context-specific policy adaptation Keywords: Malnutrition, toddlers, maternal knowledge, food intake, infectious disease, Deli Serdang, nutrition-sensitive policy